An Appraisal of Criticisms of the Brookings Institution Estimate - Mayer, Joseph; Moulton, Harold G.; Jacobstein, Meyer; Kimmel, Lewis H. (The Review of Economics and Statistics, 1945)
Joseph Mayer, Harold G. Moulton, Meyer Jacobstein, Lewis H. Kimmel, An Appraisal of Criticisms of the Brookings Institution Estimate, The Review of Economics and Statistics, Vol. 27, No. 4 (Nov., 1945), pp. 189-191